(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Phylogenetic trees describe the evolutionary relationships among different types of organisms. The selection of methods used in the construction of these trees is not easy because the data used is often incomplete, meaning it comes from studies of both modern organisms and fossils. Also, the morphological data can be misleading ; when closely related organisms may not look the same and distantly related organisms may share certain features, all these reasons make it difficult to determine the true relationships between these organisms. Therefore, the genetic data is more dependable, so it’s usually a preferred method used to construct phylogenetic trees. Despite that, the genetic data can be affected by several factors, such as gene transfer, loss, and the choice of genes that are used. It’s important to note that phylogenetic trees do not account for the length of time over which evolution happened ; they only reflect the order of divergence among lineages. Despite all these challenges, phylogenetic trees are still a crucial tool in understanding the evolution of life and in identifying new relationships among different organisms. Recently, the use of phylogenetic analysis in microbiological research has increased significantly. This review provides an overview of the concept of phylogeny, the different methods used in the construction of phylogenetic trees, the applications of phylogenetic analysis in microbiology, and the steps involved in building a suitable phylogenetic tree.